Program Psikoedukasi untuk Meningkatkan Pengetahuan dan Keterampilan Guru dalam Menangani Bullying - Sigit Nugroho; M.G. Adiyanti (Universitas Islam Indonesia, 2011)
The growth of bullying behavior in schools has become a phenomena that should be taken to matters. Teacher's role in handling bullying plays an important role and their knowledge in this issue are sufficent. Therefore, there is a necessity to increase their knowledge so correct actions can be taken to place. The goal of this research is to see the effectiveness of psychoeducational program in increasing teacher's knowledge and skill to intervene bullying behavior in school. Hyphotesis of this research is psychoeducational program will increase teachers' knowledge and skill in handling bullying behavior in school. Participants are 16 teachers in experimental group and 11 teachers in the control group This research uses action research design. Psychoeducational program contains eight session, where each session's duration last for about one hour. The result of this research is that psychoeducatioanal program effective in increasing teacher's knowledge and skill in handling bullying behavior (knowiwdge: F:19,805., rf:0,442Me=14,25.Mc=-4,09;sk///: F: 6,146; rf; 0,197., Me=6,19, Mc=0,91).Keyword: Bullying, psychoeducational program, knowledge and skill